2021
DOI: 10.1186/s40468-021-00132-7
|View full text |Cite
|
Sign up to set email alerts
|

A Rasch-based validation of the Vietnamese version of the Listening Vocabulary Levels Test

Abstract: The Listening Vocabulary Levels Test (LVLT) created by McLean et al. Language Teaching Research 19:741-760, 2015 filled an important gap in the field of second language assessment by introducing an instrument for the measurement of phonological vocabulary knowledge. However, few attempts have been made to provide further validity evidence for the LVLT and no Vietnamese version of the test has been created to date. The present study describes the development and validation of the Vietnamese version of the LVLT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
(50 reference statements)
0
23
0
Order By: Relevance
“…Collected data were computed using WINSTEPS 5.1.5 (Linacre, 2021) based on the Rasch dichotomous model (Rasch, 1960). The study re-used some of the data reported in Ha (2021), of course, with the official agreement of the author.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Collected data were computed using WINSTEPS 5.1.5 (Linacre, 2021) based on the Rasch dichotomous model (Rasch, 1960). The study re-used some of the data reported in Ha (2021), of course, with the official agreement of the author.…”
Section: Discussionmentioning
confidence: 99%
“…This study involved the administration of the two VLT: the UVLT (form B) (Webb et al, 2017) and Vietnamese LVLT (Ha, 2021). The two VLT were reported to have satisfied major validation requirements in Wright and Stone (1999) comprehensive framework which consisted of reliability, separation, fit statistics, unidimensionality and local dependence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations